Bioprospecting and economical source of chitin and chitosan: the sword shrimp udang minyak (Parapenaeopsis hardwickii) Malaysia - Khan Chowdhury, Ahmed Jalal; Darnis, Deny Susanti; Husna, Suffi Nurul (2010)
Chitin and chitin derivatives (Chitosan) are biodegradable and biocompatible natural polymers that have been used in virtually every significant segment of the economy (water treatment, pulp and paper industry, biomedical devices and therapies, cosmetics and diet additives). Based on above perspectives the potential and economical sources of chitin and chitosan contents were investigated from the local sea food sources. Four different types of shrimps and crabs shell wastes namely Udang Minyak (Sword Shrimp, Parapenaeopsis hardwickii), Udang Putih (White Shrimp, Fenneropenaeus indicus), Ketam Batu, (Mud crab, Scylla serrata) and Ketam Bunga, (Blue crab, Callinectes sapidus) were collected from the wet market (Pasar Borong) of Kuantan. These samples were chosen as they were most abundant and well-liked shell fishes among the sea foods and locally available in the coastal areas of Malaysia. The chemical extraction of shrimps and crabs shell wastes showed that the percentage of chitin in udang minyak, udang putih, ketam batu and ketam bunga were 78.86%, 73.43%, 75.75% and 71.31% respectively. Whereas the percentage of chitosan in udang minyak, udang putih, ketam batu and ketam bunga were 71.61%, 64.66%, 60.59% and 52.38% respectively. The study portrays that most cheapest and abundant shrimp, udang minyak, the Sword Shrimp, Parapenaeopsis hardwickii shell wastes have the highest percentage of chitin and chitosan and the highest purity of chitin content compared to others. The study could be instrumental for wider application of higher quality chitin and chitosan in biotechnology and pharmaceutical industries by using this potential resource.